Localization of nerve growth factor-β in the stallion reproductive tract - Mickelson, Alison, author; McCue, Patrick, advisor; Graham, James, advisor; Magunda, Forgivemore, committee member (Colorado State University. Libraries, 2020)
Nerve growth factor-β (NGF-β) is a protein produced in the reproductive tract of camelids (camels, llamas, and alpacas) that has been identified as the ovulation inducing factor in seminal plasma. NGF-β from seminal plasma deposited into the reproductive tract of the female camelid acts systemically to stimulate secretion of luteinizing hormone (LH) from the anterior pituitary, which in turn induces follicle maturation and ovulation. The objectives of the present study were to 1) determine if NGF-β is present in the reproductive tract of the stallion and 2) identify the specific site(s) of production. The hypotheses were that NGF-β would be present in the stallion reproductive tract and would primarily be localized in Sertoli cells of the testis and the prostate gland. Immunohistochemistry on paraffin embedded paraformaldehyde fixed tissues was performed using a rabbit polyclonal anti-NGF-β antibody on a total of six male equine reproductive tracts, including a one-day old colt, a one-year old colt and 4 adult stallion tracts. Strong immunostaining was observed in the efferent ducts of the testis and the epithelial cells of the prostate, seminal vesicles, bulbourethral glands and ampullae. Weaker NGF-β staining was noted in Leydig cells, Sertoli cells and spermatogonia within the testes and in epithelial cells of the epididymis. In conclusion, immunohistochemistry revealed that NGF-β is present in the stallion reproductive tract and the protein is primarily present in the efferent ducts of the testes and in all accessory sex glands.